Public health and medical preparedness for mass casualties from the deliberate release of synthetic opioids - Cibulsky, Susan M.; Wille, Timo; Funk, Renée; Sokolowski, Danny; Gagnon, Christine; Lafontaine, Marc; Brevett, Carol; Jabbour, Rabih; Cox, Jessica; Russell, David R.; Jett, David A.; Thomas, Jerry D.; et al. (Frontiers in Public Health, 2023)
The large amounts of opioids and the emergence of increasingly potent illicitly manufactured synthetic opioids circulating in the unregulated drug supply in North America and Europe are fueling not only the ongoing public health crisis of overdose deaths but also raise the risk of another type of disaster: deliberate opioid release with the intention to cause mass harm. Synthetic opioids are highly potent, rapidly acting, can cause fatal ventilatory depression, are widely available, and have the potential to be disseminated for mass exposure, for example, if effectively formulated, via inhalation or ingestion. As in many other chemical incidents, the health consequences of a deliberate release of synthetic opioid would manifest quickly, within minutes. Such an incident is unlikely, but the consequences could be grave. Awareness of the risk of this type of incident and preparedness to respond are required to save lives and reduce illness. Coordinated planning across the entire local community emergency response system is also critical. The ability to rapidly recognize the opioid toxidrome, education on personal protective actions, and training in medical management of individuals experiencing an opioid overdose are key components of preparedness for an opioid mass casualty incident.